Inflation expectations and climate concern - Christoph Meinerding; Andrea Poinelli; Yves Schüler (Deutsche Bundesbank, 2022)
Using survey data from German households, we find that individuals with lower climate concern tend to have higher inflation expectations up to five years ahead. This correlation is most pronounced among individuals with extremely high inflation expectations. Evaluating candidate explanations, we find that part of the link between climate concern and inflation expectations can be associated with individuals' perceived exposures to climate-related risks and with their distrust in the central bank. Overall, our results suggest that climate change perceptions matter for inflation expectations.
Keywords: E31; E50; Q54; Q58; 330; climate change; inflation expectations; physical risk; transition risk; central bank distrust; household surveys